Lhx2 and Lhx9 determine neuronal differentiation and compartition in the caudal forebrain by regulating Wnt signaling. - Daniela Peukert; Sabrina Weber; Andrew Lumsden; Steffen Scholpp (PLoS Biology)
Initial axial patterning of the neural tube into forebrain, midbrain, and hindbrain primordia occurs during gastrulation. After this patterning phase, further diversification within the brain is thought to proceed largely independently in the different primordia. However, mechanisms that maintain the demarcation of brain subdivisions at later stages are poorly understood. In the alar plate of the caudal forebrain there are two principal units, the thalamus and the pretectum, each of which is a developmental compartment. Here we show that proper neuronal differentiation of the thalamus requires Lhx2 and Lhx9 function. In Lhx2/Lhx9-deficient zebrafish embryos the differentiation process is blocked and the dorsally adjacent Wnt positive epithalamus expands into the thalamus. This leads to an upregulation of Wnt signaling in the caudal forebrain. Lack of Lhx2/Lhx9 function as well as increased Wnt signaling alter the expression of the thalamus specific cell adhesion factor pcdh10b and lead subsequently to a striking anterior-posterior disorganization of the caudal forebrain. We therefore suggest that after initial neural tube patterning, neurogenesis within a brain compartment influences the integrity of the neuronal progenitor pool and border formation of a neuromeric compartment.